2021
DOI: 10.1016/j.jcf.2021.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Design and methods for understanding the state of cystic fibrosis care amid the COVID-19 pandemic

Abstract: Background Novel therapies have dramatically changed cystic fibrosis (CF) and innovative care delivery systems are needed to meet future patient needs. Telehealth has been shown to be an efficient and desirable form of care delivery. The COVID-19 pandemic caused a rapid shift to telehealth, and this presented a unique opportunity to study facilitators, barriers, and satisfaction with this mode of care delivery. We aim to report survey methods, demographics and telehealth use among CF care programs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…1 During the COVID-19 pandemic, there was a rapid shift to telehealth services to maintain access to ambulatory care. 2 PwCF were eager for solutions to the limited in-person assessments 3 and there was widespread adoption of home spirometry in the CF population in the United States 4 and globally. 5 Prior validation studies of various devices demonstrated concordance to in-clinic measures in a supervised setting, 6,7 with conflicting findings of accuracy in an unsupervised setting.…”
mentioning
confidence: 99%
“…1 During the COVID-19 pandemic, there was a rapid shift to telehealth services to maintain access to ambulatory care. 2 PwCF were eager for solutions to the limited in-person assessments 3 and there was widespread adoption of home spirometry in the CF population in the United States 4 and globally. 5 Prior validation studies of various devices demonstrated concordance to in-clinic measures in a supervised setting, 6,7 with conflicting findings of accuracy in an unsupervised setting.…”
mentioning
confidence: 99%
“…Um estudo realizado por Dowd et al (2021) nos Estados Unidos mostra uma abordagem ampla do uso dos serviços de telessaĂșde no perĂ­odo mais crĂ­tico da pandemia, voltados para o atendimento de pessoas com FC, onde eram oferecidos por programas de tratamento vĂĄrios nĂ­veis de serviços, que tiveram boa aceitação pela população, sendo que cerca de 50% aderiram a essa forma de consultas remotas. Ademais, foi possĂ­vel observar os bons resultados do sistema, que contribuĂ­ram para redução das perdas ocasionadas pela suspensĂŁo das consultas e tratamentos.…”
Section: Discussionunclassified
“…The SARS-2-CoV2 pandemic has led to significant changes in health care delivery for PwCF. A widespread surge in ‘tele’ or digital health has occurred [ 6 , 7 ]. In general, this has been reasonably successfully implemented and accepted by PwCF and care providers, particularly adults [8] , [9] , [10] , [11] , [12] .…”
Section: Impact Of Covid-19 On Clinical Carementioning
confidence: 99%
“…Disparities in high speed internet access and technology may create a ‘digital divide' [ 9 , 12 , 17 ]. Whilst the surge in telehealth has subsided and confidence in returning to face to face visits has grown, in person consultations will probably not return to pre pandemic levels [ 6 , [10] , [11] , [12] , [13] , [14] ]. Health care delivery has evolved and there is much work to do with evaluation and implementation of new hybrid models that address the individual needs of PwCF.…”
Section: Impact Of Covid-19 On Clinical Carementioning
confidence: 99%